2009
DOI: 10.1007/s10750-009-0033-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of otolith chemistry for identifying source environment of fishes in the lower Illinois River, Illinois

Abstract: Knowledge of habitats used by fish throughout their life history is important for management and conservation of riverine fish populations and habitats. Naturally occurring chemical markers in otoliths have recently been used to determine natal origins and environmental history of fishes in a variety of marine and freshwater environments.However, to our knowledge no studies have examined the applicability of this technique in large floodplain rivers in the U.S.A. We evaluated otolith microchemistry and stable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
59
1
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(79 citation statements)
references
References 50 publications
14
59
1
5
Order By: Relevance
“…1) (Kendall & Caldwell, 1998 (Zeigler and Whitledge 2010). Fishes were captured by alternating current (AC) or direct current (DC) electrofishing or trap netting at sites where a boat could be launched.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1) (Kendall & Caldwell, 1998 (Zeigler and Whitledge 2010). Fishes were captured by alternating current (AC) or direct current (DC) electrofishing or trap netting at sites where a boat could be launched.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, association of otolith biochronology with isotopic and elemental composition enables retrospective description of fish environmental history when an individual has resided in chemically distinct locations for a period of time sufficient to incorporate the signature of those sites (Kennedy et al, 2002). Crook & Gillanders (2006) demonstrated the applicability of otolith microchemistry for identifying common carp recruitment sources in the Murray River, Australia, and Zeigler & Whitledge (2010) confirmed that stable isotopic signatures in otoliths can be used to reliably identify environment of origin (river, floodplain lake, or tributary) for fishes in the Illinois River, Illinois. However, the applicability of otolith trace element and stable isotopic signatures as natural markers of fish environmental history in the Mississippi River and associated water bodies has not been assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Otolith strontium:calcium (Sr:Ca) ratios and stable oxygen isotopic compositions are strongly correlated with those of the environment occupied by a fish (Wells et al 2003;Zeigler and Whitledge 2010;Smith and Whitledge 2011 (Patterson et al 1993). Association of otolith biochronology with isotopic or elemental composition enables retrospective description of fish environmental history (e.g., identification of natal environment from the portion of the otolith accreted during early life) when an individual has resided in chemically distinct locations for a period of time sufficient to incorporate the signature of those sites (Kennedy et al 2002;Dufour et al 2005;Whitledge et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Differences in stable oxygen isotope ratios between the Illinois River and its floodplain lakes also enable identification of fish use of floodplain lake habitats (Zeigler and Whitledge 2010). Thus, otolith chemistry should be applicable for identifying recruitment sources of Bighead Carp and Silver Carp in the Illinois River.…”
Section: Introductionmentioning
confidence: 99%
“…Certaines ont tenté plus particulièrement de mettre en relation la composition élémentaire des otolithes avec celle de l'eau (Bath et al, 2000;Elsdon et Gillanders, 2003;Milton et Chenery, 2001 (Brazner et al, 2004b). Jusqu'à présent, l'empreinte élémentaire a surtout été utilisée en milieux marins (Brown, 2006;Campana et al, 2007;Clarke et al, 2009;Cook, 2011;Edmonds et al, 1991;Fodrie et Herzka, 2008;Gillanders et Kingsford, 1996;Humphreys Jr et al, 2005;Lawton et al, 2010;Rooker et al, 2002;Thorrold et al, 2007), dans certains estuaires (Bradbury et al, 2011;Brown, 2006;Gillanders et Kingsford, 1996;Hobbs et al, 2007;Swearer et al, 2003) et seulement quelques recherches comparables ont été menées en eaux douces avec succès (Brazner et al, 2004a;Brazner et al, 2004b;Fisher et al, 1999;Whitledge, 2009;Zeigler et Whitledge, 2010;Zeigler et Whitledge, 2011;Zitek et al, 2010). heures pour un séchage complet, puis rangées dans une boîte en vue de procéder aux analyses à l'aide d'un spectromètre de masse couplé à un plasma inductif (Tableau 2).…”
Section: Remerciementsunclassified